Neurogenesis in the embryonic and adult brain: same regulators, different roles - Urbán, Noelia; Guillemot, François (Frontiers in Cellular Neuroscience, 2014)
Neurogenesis persists in adult mammals in specific brain areas, known as neurogenic niches. Adult neurogenesis is highly dynamic and is modulated by multiple physiological stimuli and pathological states. There is a strong interest in understanding how this process is regulated, particularly since active neuronal production has been demonstrated in both the hippocampus and the subventricular zone of adult humans. The molecular mechanisms that control neurogenesis have been extensively studied during embryonic development. Therefore, we have a broad knowledge of the intrinsic factors and extracellular signalling pathways driving proliferation and differentiation of embryonic neural precursors. Many of these factors also play important roles during adult neurogenesis, but essential differences exist in the biological responses of neural precursors in the embryonic and adult contexts. Because adult neural stem cells are normally found in a quiescent state, regulatory pathways can affect adult neurogenesis in ways that have no clear counterpart during embryogenesis. BMP signalling, for instance, regulates neural stem cell behaviour both during embryonic and adult neurogenesis. However, this pathway maintains stem cell proliferation in the embryo, while it promotes quiescence to prevent stem cell exhaustion in the adult brain. In this review, we will compare and contrast the functions of transcription factors and other regulatory molecules in the embryonic brain and in adult neurogenic regions of the adult brain in the mouse, with a special focus on the hippocampal niche and on the regulation of the balance between quiescence and activation of adult neural stem cells in this region.